2014
DOI: 10.1089/zeb.2013.0926
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lighting Conditions on Zebrafish Growth and Development

Abstract: In the underwater environment, the properties of light (intensity and spectrum) change rapidly with depth and water quality. In this article, we have described how and to what extent lighting conditions can influence the development, growth, and survival of zebrafish. Fertilized eggs and the corresponding larvae were exposed to different visible light wavelengths (violet, blue, green, yellow, red, and white) in a 12-h light-12-h dark (LD) cycle until 30 days posthatching (dph), when the expression of morphomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
111
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(122 citation statements)
references
References 64 publications
9
111
2
Order By: Relevance
“…Similar delays in development related to reduced light and temperature have been previously reported by several authors (Schirone and Gross, 1968; Billotta, 2000; Villamazar et al, 2014; Di Rosa et al, 2015). Notably, for example, Billotta (2000) investigated effects of light on various aspects of zebrafish embryo development, and found that embryos raised in constant dark were generally “developmentally delayed,” and specifically “were still not hatched by 7 dpf.” Subsequent studies have, likewise, shown developmental delay due to rearing in constant dark including various consequent post-larval effects (Villamazar et al, 2014; Di Rosa et al, 2015). Alongside delayed development, relatively high embryotoxicity within 1–2 dpf was observed for all embryos (including controls) reared in constant dark, as specifically evidenced by coagulation, and independent of the generally lethal deformities.…”
Section: Resultssupporting
confidence: 90%
“…Similar delays in development related to reduced light and temperature have been previously reported by several authors (Schirone and Gross, 1968; Billotta, 2000; Villamazar et al, 2014; Di Rosa et al, 2015). Notably, for example, Billotta (2000) investigated effects of light on various aspects of zebrafish embryo development, and found that embryos raised in constant dark were generally “developmentally delayed,” and specifically “were still not hatched by 7 dpf.” Subsequent studies have, likewise, shown developmental delay due to rearing in constant dark including various consequent post-larval effects (Villamazar et al, 2014; Di Rosa et al, 2015). Alongside delayed development, relatively high embryotoxicity within 1–2 dpf was observed for all embryos (including controls) reared in constant dark, as specifically evidenced by coagulation, and independent of the generally lethal deformities.…”
Section: Resultssupporting
confidence: 90%
“…Means were contrasted using the Tukey methods and different lowercase letters indicate significant differences between each treatment (p < 0.05) Villamizar et al, 2013). Data were analysed using a two-way full factorial ANOVA model, where light intensity (A) and light spectrum (B) had a significant effect.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in other species have shown that de novo cortisol synthesis starts shortly after hatching, and a significant elevation in whole body cortisol in response to various stressors becomes obvious days to weeks later (usually close to first feeding), depending on the species (Alsop & Vijayan, 2008;Applebaum, Wilson, Holt, & Nunez, 2009;Barry, Malison, Held, & Parrish, 1995;Deane & Woo, 2003;Jentoft, Held, Malison, & Barry, 2002;Szisch, Papandroulakis, Fanouraki, & Pavlidis, 2005). When Villamizar et al (2013) investigated the effects of lighting conditions on zebrafish growth and development, they also found that the expression of stress factors was upregulated in the violet (pomca, and crh) group, which is consistent with the higher growth recorded under the violet light. Previous studies proposed that under acute stress, crh mRNA expression decreased considerably, suggesting that the regulation of this gene expression is controlled by increased glucocorticoid levels through a genomic feedback mechanism (Bernier, Lin, & Peter, 1999;Dallman et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although only one male valopa mutant was available for examination, late hatching was also observed in the surviving embryos from F0 female valopb rw01 and valopb rw02 mutants. Interestingly, recent studies showed that ambient light conditions affect zebrafish hatching; specifically, light deprivation and the exposure to red light delay hatching of WT embryos [48, 49]. Therefore, we expected that non-functional VAL-opsin was the cause of delayed hatching of the F1 embryos.…”
Section: Discussionmentioning
confidence: 93%